(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The combined use of organic and inorganic fertilizer combination and gibberellic acid (GA3) is a potential solution to increase yields. The motives of this investigation are to evaluate the yield and yield attributes of mustard varieties with different fertilizer combinations and gibberellic acid (GA3). The experiment was set at the Research Field of the Department Crop Physiology and Ecology of Hajee Mohammad Danesh Science and Technology University, Dinajpur, in accordance with randomized complete block design with three replications. Three mustard varieties viz., BARI mustard-14, BARI mustard-17 and BINA mustard-9 were evaluated against four combined fertilizations and GA3. The maximal yield and yield attributing traits were significantly subjugated by variant fertilization and varieties. The results expounded that BARI mustard-17 emanated the utmost values followed by varieties BARI mustard-14 and BINA mustard-9. In extent of fertilization, most of the growth parameters showed the highest values in Urea: 250 kg ha-1, MoP: 70 kg ha-1, TSP: 190 kg ha-1, Gypsum: 120 kg ha-1, Zinc Sulphate: 4 kg ha-1, Boric acid: 10 kg ha-1, Poultry litter compost: 10 tons ha-1, GA3: Gibberellic Acid 10 % and the lowest values were recorded in Urea: 250 kg ha-1, MoP: 70 kg ha-1, TSP: 190 kg ha-1, Gypsum: 120 kg ha-1, Zinc Sulphate: 4 kg ha-1, Poultry litter compost: 10 tons ha-1. In the majority of instances, the BARI mustard-17 and Urea: 250 kg ha-1, MoP: 70 kg ha-1, TSP: 190 kg ha-1, Gypsum: 120 kg ha-1, Zinc Sulphate: 4 kg ha-1, Boric acid: 10 kg ha-1, Poultry litter compost: 10 tons ha-1, GA3: Gibberellic Acid 10 % exhibited the highest performance in the context of fertilization and variety interactions. J Bangladesh Agril Univ 22(2): 185-192, 2024